Development of marketing capabilities in electronic commerce and effectiveness - Babahkan, Vajiheh (Opción, 2019)
The aim of the study is to investigate development of marketing capabilities in electronic commerce and effectiveness to enhance the performance of financial and credit institutions. This study is a descriptive by method and is a correlational-survey. As a result, there is a positive correlation between branch performance and marketing capabilities. Besides, the component of high public relations (communication) has the lowest average score. In conclusion, banks can increase their public relations in a variety of ways in order to convey important messages to its customers.